Penggunaan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Peserta Didik Kelas Rendah di SDN 94 Palembang - Putriani, Muspa; Nurhasana, Selvi; Utami, Tri; Siskamia, Siskamia; Wahyuni, Yuyun; Fathurohman, Apit; Dakim, Dakim; Fatikhah, Wiwin Nafiatul (Universitas Batanghari Jambi, 2025)
This research aims to explore the use of the Problem Based Learning (PBL) learning model in improving student learning outcomes at SD Negeri 94 Palembang. The method used was classroom action research (PTK) which was carried out in two classes with two cycles of treatment, involving 23 students from classes I.B, II.A and II.B. Data is collected through learning outcomes tests in the form of multiple choices. The research results show that the application of the PBL model significantly improves student learning outcomes regarding Indonesian language material. The learning outcomes of class I.B students in the first cycle obtained an average score of 81.7, and in the second cycle students showed an increase in learning outcomes with an average of 86.5. Furthermore, class II.A in the first cycle obtained an average score of 80, then in the second cycle students experienced an increase in learning results with an average score of 88.4. Then in the first cycle in class II.B, there was an average score of student learning outcomes of 81.3, and in the second cycle student learning outcomes showed better progress of 86.7. So based on the results of this classroom action research, it can It is concluded that the PBL model can improve student learning outcomes in learning.